KARAKTERISTRIK DARI SEMIGRUPYANG SETIAPBI-IDEALNYAPRIME KUAT - Nani Kurniati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2009)
Abstrak. Dalam tulisan ini akan dibahas tentang hubungan antara bi-ideal prime kuat, bi-ideal prime, bi-ideal semiprime, bi-ideal tak terreduksi kuat, dan bi-ideal tak terreduksi dari semigrup. Selain itu juga akan dibahas tentang karakteristik dari semigrup yang setiap bi-idealnya prime kuat.Kata-kata Kunci : Bi-ideal prime kuat, bi-ideal prime, bi-ideal semiprimeAbstract. In this paper, we introduce the strongly prime, prime, semi-prime, strongly irreducible and irreducible bi-ideals of semi-groups. We also characterize those semi-groups for which each bi-ideal is strongly prime.Keywords : Strongly prime bi-ideals, prime bi-ideals , semiprime bi-ideals